Diverse Perspectives in Islamic Banking and Finance: Insights from Indonesia - Azharsyah Ibrahim (Share: Jurnal Ekonomi dan Keuangan Islam, 2021)
In this issue, our primary focus is to ensure a prompt review and publication process for the incoming manuscripts without compromising on quality. As customary, every manuscript we receive undergoes an initial review to assess its suitability for further evaluation. We place significant emphasis on the recommendations provided by our reviewers when making the decision to accept a manuscript. It is worth noting that some authors may need to revise and resubmit their manuscripts multiple times before they meet our criteria for publication. Given the rigorous evaluation process, we have selected only eight manuscripts for publication in this issue, out of the numerous submissions received through our online system. These accepted manuscripts cover a wide range of topics within the field of Islamic economics and finance. We strive to include diverse and insightful discussions that contribute to the advancement of knowledge in this area.